Treating the Critically Ill with Radiotherapy: Lessons Learned from a Young Woman with Cardiac Angiosarcoma - Fields, Emma C.; Squires, Bryan; Lomas, Harry (Frontiers in Oncology, 2017)
Background: Treating patients who are critically ill with radiotherapy brings a unique set of challenges as it involves treating patients who require mechanical life support, unconventional positioning, and a multidisciplinary team approach to ensure safety. However, when the benefits of such treatment outweigh the risks, the challenges can be overcome, as demonstrated in this unique case of cardiac angiosarcoma. Case Description: This a a case of a 42 year old female with a right sided cardiac angiosarcoma who quickly developed cardiac tamponade and respiratory failure related to compression of her right heart by the tumor. She was treated with high dose single fraction radiotherapy initially and had a clinical response allowing further conformal radiotherapy with concurrent chemotherapy. Discussion: Managing critically ill patients requires creativity, improvisation, and careful consideration of existing evidence. Although limited, the data suggest that multi-modality therapy with a combination of surgery, radiotherapy and chemotherapy provide the best outcomes.